The effects of structural adjustment programmes - Zattler (Intereconomics, 1989)
Many developing countries are trying to improve their economic conditions by means of structural adjustment programmes. The following article points out the weaknesses of such programmes and draws conclusions about the support that should be given to economic reform in developing countries in the future.
Keywords: 330; Development Strategy